Evaluation of the Prevalence of Incidental HBV, HCV and HIV Infection Among Patients Presenting to the Emergency Department: A Prospective Cross-sectional Study - Mehmet Murat Oktay; Behçet Al; Yasemin Zer; Cuma Kılıçoğlu; Mustafa Boğan; Mustafa Sabak; Hasan Gümüşboğa (Eurasian Journal of Emergency Medicine, 2020)

(untitled)
Aim:In this study, we randomized the patients without known hepatitis-B, hepatitis C and HIV infection who presented to the emergency department (ED). We measured the serum levels of HBsAg, Anti-HCV and Anti-HIV antibodies besides biochemical tests regarding the diagnostic process of the main complaint resulting in presentation to the ED. In this way, we aimed to determine the prevalence of occult chronic viral diseases among patients presenting to the ED and the risk of ED employees was evaluated.Materials and Methods:The study included 800 patients who had presented to the ED for any reason over two month and who had no history of infectious viral disease.Results:Four hundred and thirthy-four (54.2%) of the patients were male, 366 (45.8%) were female, and the mean age was 32.7 (±16.9) years. The rate of presence of a person with an infectious viral disease at the patient’s home was 1%, 0.5% and 0.0% for HBV, HCV, and HIV, respectively. The overall history of HBV vaccination was 15.5% in our study sample. HBsAg, anti-HCV and HIV-positivity were 2%, 0.8% and 0.0%, respectively.Conclusion:The prevalence of HBV- and HCV-positivity in patients admitted to the ED who did not have any known chronic viral disease was consistent with the general population prevalence. No significant change in the prevalence of HCV compared to previous years can be explained by the absence of a protective vaccine. The absence of HIV-positivity can be explained by the low rate of HIV-positivity in our country.